The Z-octahedron family: A new tensegrity family. (1st November 2020) - Fernández-Ruiz, Manuel Alejandro; Hernández-Montes, Enrique; Gil-Martín, Luisa María
Highlights: A new family of tensegrity structures is presented: the Z-octahedron family. An analytical form-finding method is used to obtain super-stable tensegrities. The Z-double-expanded octahedron can be defined by geometrical intuition from a truncated cube. Abstract: A new family of tensegrity structures is presented: the Z-octahedron family. A tensegrity family is a group of tensegrity structures that share a common connectivity pattern. The members of the Z-octahedron family have been obtained replacing the elementary rhombic cells of the members of the octahedron family with elementary Z-shaped cells. In addition, a higher number of possible force density or force:length ratio values have been considered. The values of the force:length ratio of the members of the family that lead to super-stable tensegrity forms have been computed analytically. Two members of the family have been obtained: the Z-expanded octahedron and the Z-double-expanded octahedron. Finally it has been proved that the Z-double-expanded octahedron obtained here from topological rules can also be defined from a truncated cube based on purely geometrical intuition.